Do fiscal rules cause budgetary outcomes? - Signe Krogstrup; Sébastien Wälti (Graduate Institute of International Studies, 2007)
This paper focuses on the observed empirical relationship between fiscal rules and budget deficits, and examines whether this correlation is driven by an omitted variable, namely voter preferences. We make use of two different estimation methods to capture voter preferences in a panel of Swiss sub-federal jurisdictions. First, we include a recently constructed measure of fiscal preferences. Second, we capture preferences through fixed effects with a structural break as women are enfranchised. We find that fiscal rules continue to have a significant impact on real budget balances.
Keywords: C2; D7; E6; H6; 330; fiscal policy; fiscal rules; fiscal institutions; budget deficits; fiscal preferences; endogeneity; Finanzpolitik; Regelbindung; Haushaltsdefizit; Theorie; Schweiz